Students’ challenges of writing science essays in English for Specific Purposes at tertiary level - Pastushenko, Tetiana; Lutkovska, Nataliia (ScienceRise: Pedagogical Education, 2026)
Analyzing and summarizing information from different sources, comparing and contrasting ideas, interpreting and presenting results are routine job-related issues stipulating an integrated approach to the development of linguistic and specialism-related competences of majors in Biology used to describe scientific theories and models, discuss and evaluate experimental methods. These tasks are highly correlated with academic writing skills that, to a great extent, can be acquired by constructing academic specialism-related essays. The objective of this paper is to identify and analyze the difficulties of majors in Biology in science essay writing in English at intermediate level and suggest successful strategies that can be employed to solve the problems arising. The research was conducted within the framework of an ESP course for junior students. In order to visualize the challenges, 30 undergraduates were involved in writing 3 different types of science essays as a part of their formative assessment. At the next stage of the research, these papers were subjected to qualitative and quantitative analyses. The complexities experienced by undergraduates are divided into: 1) defining the relevant essay type and composing parts of the essay; 2) lingual instruments of arranging ideas. The findings of this research indicate that the appropriate communicative strategy employed by students when identifying the essay type essentially contributes to crafting relevant content. Constructing an effective introduction and ensuring text cohesion, followed by building a successful conclusion and making relevant references to the data and visuals, epitomize the highest level of difficulties in writing science essays in English for Specific Purposes